Strychnine poisoning in a dog - Abdullah, Abdul Salam; Abdul Rahman, Sheikh Omar; Ibrahim, Rashid (Persatuan Doktor Veterinar Malaysia, 1985)
A case of strychnine poisoning in a dog characterized by sudden death, rapid occurrence of rigor mortis and lack of specific pathological changes is reported. Biologic verification in mice was positive for strychnine poisoning when extract of stomach content from the dead dog, injected intraperitoneally, resulted in death of the mice within five minutes with characteristic signs. A white powder in a mutilated cigarette case found on the field where this dog had been playing also resulted in death of mice during a similar verification procedure.